Terjebak di dunia game / gambar, Ebit Jatayu, Faisal A.S., Mutia Rizanati; cerita, Assyifa S. Arum; penyunting, Ahmad Mahdi - EBIT JATAYU; Faisal A.S.; Assyifa S. Arum; Ahmad Mahdi (Dar! Mizan, 2016)
85 hlm. : ilus. ; 19 cm.